A risk-stratified framework for in-house PLA 3D printing of non-critical medical device spare parts: a cost-effectiveness analysis - Kun Li; Xinghua Ma; Lei Su; Yinyan Sun; Qian Mu; Dingmeng Luo; Jing Cheng (Frontiers in Medicine, 2026)
Background Procurement of non-critical medical device spare parts faces major challenges. These include high costs, long lead times, and supply chain fragility. In-house additive manufacturing (AM), specifically Polylactic Acid (PLA) Fused Deposition Modeling (FDM), offers a potential solution but lacks systematic safety and economic validation. Objective This study aimed to establish a risk-stratified framework for identifying suitable non-critical spare parts and to evaluate the engineering feasibility, economic impact, and operational implications of in-house PLA FDM 3D printing. Methods A three-dimensional risk classification matrix (Functional, Contact, Load; F-C-L) was developed to screen eligible parts (F0, L0, C ≤ C1). Forty-two part models were selected. Engineering evaluations were conducted. These assessed dimensional accuracy, assembly fit, and simulated reliability. A comprehensive economic analysis was performed. It compared in-house printing with traditional OEM procurement. Metrics included unit cost, lead time, downtime, and estimated benefits. Results The mean dimensional error was 0.18 ± 0.07 mm. All deviations remained within the ±0.5 mm tolerance. The first-print installation success rate was 92.9%, reaching 100% after minor adjustments. User-perceived performance was rated as comparable or acceptable. All parts passed scenario-specific durability tests (e.g., 20,000 press cycles for buttons). Economically, unit costs dropped significantly. 3D-printed parts cost CNY 66.86 vs. CNY 530.92 for OEM parts ( P < 0.001), an 87.4% reduction. Supply lead time fell drastically from 202.8 h to 11.9 h ( P < 0.001). This yielded a 94.1% reduction in annual downtime for the 20 representative parts analyzed. The estimated annual economic benefit was approximately CNY 2.66 million. The return on investment was high. Sensitivity analyses confirmed the robustness of these cost advantages. Conclusion Within clearly defined safety boundaries, in-house PLA FDM 3D printing is technically viable. It is also economically advantageous. The proposed F-C-L risk matrix provides a pragmatic framework. It enhances hospital supply chain resilience and operational efficiency.